2019
DOI: 10.2174/1871520619666190507100912
|View full text |Cite
|
Sign up to set email alerts
|

STK33-dependent transcriptional regulation of SFTA3 induces Cisplatin-resistance in lung adenocarcinoma

Abstract: : Drug-resistance has become a major obstacle for Cisplatin usage in non-small cell lung cancer. In this study, we identified a poorly-studied kinase Serine/Threonine Kinase 33 (STK33) as the most up-regulated kinase encoding gene in Cisplatin resistant lung adenocarcinoma. Additionally, STK33-dependent Cisplatin-resistance promotes tumor growth of lung adenocarcinoma both in vitro and in vivo. Clinically, STK33 expression was enriched in lung adenocarcinoma and was correlated to poor prognosis of lung cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…STK33, a member of the protein kinase superfamily, phosphorylates serine and threonine residues on proteins which plays a key role in regulating some important cellular processes, such as signal transduction pathway, DNA replication, cell differentiation, cell proliferation, cell death and tumor development (10,11). The expression of STK33 in pancreatic cancer, lung cancer, and liver cancer was signi cantly higher than that in corresponding non-cancerous tissues, indicating that the high expression of STK33 is closely related to the occurrence and development of pancreatic cancer, lung cancer and liver cancer (12)(13)(14). In the early stage of familial hereditary melanoma, the whole exon sequencing showed that STK33 was one of the 20 gene mutations, which suggested that STK33 played a role in its occurrence (15).…”
Section: Introductionmentioning
confidence: 99%
“…STK33, a member of the protein kinase superfamily, phosphorylates serine and threonine residues on proteins which plays a key role in regulating some important cellular processes, such as signal transduction pathway, DNA replication, cell differentiation, cell proliferation, cell death and tumor development (10,11). The expression of STK33 in pancreatic cancer, lung cancer, and liver cancer was signi cantly higher than that in corresponding non-cancerous tissues, indicating that the high expression of STK33 is closely related to the occurrence and development of pancreatic cancer, lung cancer and liver cancer (12)(13)(14). In the early stage of familial hereditary melanoma, the whole exon sequencing showed that STK33 was one of the 20 gene mutations, which suggested that STK33 played a role in its occurrence (15).…”
Section: Introductionmentioning
confidence: 99%